A PRELIMINARY STUDY OF HALAL LOGISTICS ISSUES AMONG FOOD MANUFACTURING COMPANIES (Journal of Technology and Operations Management, 2016)
This paper is presenting some issues encountered on halal logistics mainly for food products as to ensure the integrity status along the supply-chain network. Since halal is applicable for the Muslim and also to the non-Muslim, it makes it imperative that halal products were recognized and known globally especially for health, safety and hygiene. With a view of that, a study on halal logistics is extremely important in ensuring the concept of halal is not only applicable for preparation of food, but also the process of managing its storage, handling of raw materials, procurement, and transport. Those processes include all types of food throughout the supply-chain network with a compliance with the Shariah principles. The method used for the study is coming from a qualitative approach involving a series of interviews and supported by secondary data. The results from the study would contribute some of the novel findings in the halal logistics areas as well as suggestions for the future studies. The results were also recommended to be further discussed for the benefits and future practices of halal logistics companies in understanding the halal concept.